Modeling and control of a bedside cable-driven lower-limb rehabilitation robot for bedridden individuals - Wang, Daoyu; Li, Jicai; Jian, Zhuo; Su, Hao; Wang, Hongbo; Fang, Fanfu (Frontiers in Bioengineering and Biotechnology, 2023)
Individuals with acute neurological or limb-related disorders may be temporarily bedridden and unable to go to the physical therapy departments. The rehabilitation training of these patients in the ward can only be performed by therapists manually because the space in inpatient wards is limited. This paper proposes a cable-driven bedside lower limb rehabilitation robot based on sling exercise therapy theory. The robot can actively drive the hip and knee motions at the bedside by flexible cables linking the knee and ankle joints. A human-cable coupling controller was designed to improve the stability of the human-machine coupling system. The controller dynamically adjusts the impedance coefficient of the cable driving force based on the impedance identification of the human lower limb joints, thus realizing the stable motion of the human body. The experiments with five participants showed that the cable-driven rehabilitation robot effectively improved the maximum flexion of hip and knee joints reach to 85 • and 90 • , respectively. The mean annulus width of the knee joint trajectory was reduced by 63.84%, and the mean oscillation of the ankle joint was decreased by 56.47%, which demonstrated that human joint impedance identification for cable-driven control can effectively stabilize the motion of the human-cable coupling system.